Unusual metastases from differentiated thyroid cancers: A multicenter study in Korea - Yoon, Jee Hee; Jeon, Min Ji; Kim, Mijin; Hong, A. Ram; Kim, Hee Kyung; Shin, Dong Yeob; Kim, Bo Hyun; Kim, Won Bae; Shong, Young Kee; Kang, Ho-Cheol (PloS one, 2020)
Although infrequent, distant metastasis from differentiated thyroid cancer is the main cause of mortality in patients and mostly involves the lung, bone, and brain. Distant metastases to other sites in differentiated thyroid cancer patients are rare, thus, the clinical course of unusual metastases has not been adequately researched. In the present study, the clinico-pathological findings and treatment outcomes of unusual metastases in differentiated thyroid cancer patients in Korea were evaluated. We retrospectively reviewed the medical records of differentiated thyroid cancer patients with unusual metastases in four Korean tertiary hospitals (Chonnam National University Hwasun Hospital, Asan Medical Center, Busan National University Hospital, Severance Hospital). Unusual metastases were diagnosed using (1) cytology or histology and/or (2) imaging studies including fluorodeoxyglucose F 18 positron emission tomography/computed tomography and/or iodine 131 whole body scans with simultaneously elevated serum levels of thyroglobulin. The pathological findings of primary thyroid cancer, diagnostic method for unusual metastases, and treatment responses of unusual metastases were examined. In all, 25 unusual metastatic foci of 19 patients were analyzed; 13 patients (68.4%) had papillary thyroid carcinoma including 4 follicular variant papillary thyroid carcinomas. The median time interval between the first diagnosis of primary thyroid cancer and unusual metastases diagnosis was 110 months (11.0-138.0 months). Only 4 patients (21.1%) had synchronous unusual metastases and 6 patients (31.6%) were symptomatic. Unusual metastases included 19 metastases to solid organs (6 to kidney, 5 to liver, 4 to pancreas, 3 to adrenal gland, and 1 to ovary) and 6 to the skin and muscles. Unusual metastases were pathologically proven in 10 patients (52.6%) and 11 of 16 patients (68.8%) who received iodine 131 whole body scans had radioiodine-refractory differentiated thyroid cancer. Among 5 patients treated with tyrosine kinase inhibitors, 4 treated with lenvatinib showed stable disease or a partial response at the first treatment response. Six patients (31.6%) died due to disease progression during the median 20.0-month follow-up period (11.0-55.0 months). Unusual metastases from differentiated thyroid cancer are thought to be underestimated due to disease rarity and their metachronous nature with other distant metastases. The most of unusual metastases in differentiated thyroid cancer patients are existed with usual distant metastasis and clinical outcomes of those could not be significantly different from the prognosis of usual distant metastasis.